Organização da informação em bibliotecas: a relevância da gestão da informação nesse processo - ANJOS, Manuele Carneiro dos (2021)
Approaches information as one of the main factors for the continuous human evolution. It also demonstrates its importance and how throughout the centuries it has become notorious for the formation of societies, from being abstract and becoming concrete. Emphasizes that the intense production of information needs to be organized in a useful way for future access. It specifies the technical treatment by which the information is passed, and explains each step and exposes its value to a quality organization. The organization of information is one of the main processes developed in the library. Emphasizes that good information management streamlines technical processing and enables better interaction between librarians and users. It highlights the use of technologies as main tools for management assistance. The applied methodology is based on bibliographical research, observation and field research. Its conclusion is to demonstrate the importance of good information management for the continuous development of libraries.